2001
DOI: 10.1126/science.1060496
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Correlate of Working Memory in the Monkey Primary Visual Cortex

Abstract: A neural correlate of working memory in the monkey primary visual cortex Lamme, V.A.F.; Suphr, H.; Spekreijse, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
168
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(184 citation statements)
references
References 11 publications
16
168
0
Order By: Relevance
“…For example, it is possible that those primary areas not only represent modalityspecific sensory information while a stimulus is presented, but also are able to maintain some of that information ''on line'' during the working memory period of a discrimination task, and perhaps even participate in the subsequent decision-making steps. For instance, there are several reports suggesting that primary sensory cortices are involved to some degree in working memory tasks (34)(35)(36). Furthermore, a recent study has shown that, in addition to representing acoustic features, responses in A1 and R auditory fields may serve to encode some cognitive task elements associated with auditory processing (29), which also seems consistent with the idea that auditory cortex becomes selective to other sensory modalities when these are associated with auditory processing during action selection (29).…”
Section: Discussionsupporting
confidence: 62%
“…For example, it is possible that those primary areas not only represent modalityspecific sensory information while a stimulus is presented, but also are able to maintain some of that information ''on line'' during the working memory period of a discrimination task, and perhaps even participate in the subsequent decision-making steps. For instance, there are several reports suggesting that primary sensory cortices are involved to some degree in working memory tasks (34)(35)(36). Furthermore, a recent study has shown that, in addition to representing acoustic features, responses in A1 and R auditory fields may serve to encode some cognitive task elements associated with auditory processing (29), which also seems consistent with the idea that auditory cortex becomes selective to other sensory modalities when these are associated with auditory processing during action selection (29).…”
Section: Discussionsupporting
confidence: 62%
“…Although the functional significance of NT changes is not clear, it might be of relevance that two other neuropeptides interacting with the dopaminergic system, Calcitonin gene-related peptide (CGRP) and substance P are also decreased by risperidone and unaffected by haloperidol (Gruber and Mathé 1999). In view of interactions between working memory, a prefrontal cortex task, and visual attention tasks, localized in the occipital cortex (de Fockert et al 2001;Supèr et al 2001) and the observations that these processes are deranged in schizophrenia, selective effects of risperidone on NT, CGRP and substance P might constitute biological correlates of its beneficial effects on cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional significance of NT changes is not clear, it might be of relevance that two other neuropeptides interacting with the dopaminergic system, Calcitonin gene-related peptide (CGRP) and substance P are also decreased by risperidone and unaffected by haloperidol (Gruber and Mathé 1999). In view of interactions between working memory, a prefrontal cortex task, and visual attention tasks, localized in the occipital cortex (de Fockert et al 2001;Supèr et al 2001) and the observations that these processes are deranged in schizophrenia, selective effects of risperidone on NT, CGRP and substance P might constitute biological correlates of its beneficial effects on cognitive processes.As far as the microdialysis results, haloperidol and the higher dose of risperidone decreased basal extracellular NT-LI levels in the VSTR. These findings are in line with results showing decreased extracellular NT-LI concentrations in the nucleus accumbens and the caudate putamen following treatment with eticlopride, a DA-D 2 receptor antagonist (Wagstaff et al 1996a).…”
mentioning
confidence: 99%
“…Specifically, we show that alpha-band oscillations can be used to track when a memory representation changes its state from a passive long-term memory to an active working memory (44). Given the evidence that the similar patterns of neural activity represent perceptual inputs and maintain those representations in working memory (45)(46)(47), we propose that the alpha-band activity we measured indicates a shift to the same active state by the neurons that store longterm memories.…”
Section: Discussionmentioning
confidence: 99%